2013
DOI: 10.1186/1476-511x-12-184
|View full text |Cite
|
Sign up to set email alerts
|

A single-nucleotide polymorphism in the proximal promoter region of the apolipoprotein M gene is associated with dyslipidaemia but not increased coronary artery diseases in Chinese populations

Abstract: BackgroundIt has been reported that rs940494 and rs805296 SNPs of apolipoprotein M (apoM) gene may confer the risk in the development of type 2 diabetes (T2D) and coronary artery disease (CAD) in the Han Chinese. However, a recent study demonstrated that rs805297 polymorphism is significantly associated with reduced total high density lipoprotein (HDL) levels in rheumatoid arthritis patients. But the relationship between rs805297 SNP and CAD has not been explored. The aim of the present study was to elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It is caused by myocardial cell death due to prolonged ischemia [3]. MI is a multifactorial, polygenic disorder driven by interactions of an individual's genetic background and several environmental factors [4][5][6][7]. Greater understanding of MI etiology is mandatory to identify individuals at high risk and to improve prevention and therapy of this common and important condition.…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by myocardial cell death due to prolonged ischemia [3]. MI is a multifactorial, polygenic disorder driven by interactions of an individual's genetic background and several environmental factors [4][5][6][7]. Greater understanding of MI etiology is mandatory to identify individuals at high risk and to improve prevention and therapy of this common and important condition.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in ischaemic stroke, this polymorphism is reported to be associated with higher risk of disease development (39). Others, however, found no role of ApoM rs805297 polymorphism in development of coronary artery disease (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis needs to be further investigated. Similarly, studies on CAD also showed that the ApoM rs805297 polymorphism was not associated with ApoM plasma levels (40,41). As the control of gene expression is a very complex phenomenon that is regulated at many levels, this inconsistency may arises from the fact that in addition to this polymorphism, there are many other factors that are involved in the expression of ApoM gene, i. e. transcription factors, microRNAs (miRNAs) and small interfering RNAs (siRNAs) (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some controversies on the effects of those SNPs, with reports that support the different frequency distributions of SNPs among diverse races and nationalities [12,16,17]. More data on the effects of the apoM polymorphism with obesity and obesity-related diseases through future studies should be accumulated based on race in order to identify its causality.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the apoM T-778C SNP altered promoter activity and conferred susceptibility to type 1 diabetes in both Han Chinese and Swedish populations [15]. Although some studies reported that those SNPs did not significantly affect the development of those diseases [16,17], it is still valuable to investigate the relationship of apoM gene SNP with CAD and diabetes. ApoM T-855C and T-778C SNPs are found to be related with CAD and diabetes; however, the association of apoM polymorphism with obesity has not been reported.…”
Section: Introductionmentioning
confidence: 99%